2004
DOI: 10.1007/s00204-004-0619-3
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous metabolism of glycol ethers

Abstract: The toxicity of glycol ethers is associated with their oxidation to the corresponding aldehyde and alkoxyacetic acid by cytosolic alcohol dehydrogenase (ADH; EC 1.1.1.1.) and aldehyde dehydrogenase (ALDH; 1.2.1.3). Dermal exposure to these compounds can result in localised or systemic toxicity including skin sensitisation and irritancy, reproductive, developmental and haemotological effects. It has previously been shown that skin has the capacity for local metabolism of applied chemicals. Therefore, there is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 43 publications
0
27
0
2
Order By: Relevance
“…EGAEs can produce systemic toxicity, including spermatotoxic, teratogenic, and hematological effects, following oxidation to their corresponding aldehydes and alkoxyacetic acids (AAAs) by alcohol dehydrogenase (ADH) and aldehyde dehydrogenase (ALDH), respectively [13,15]. These enzymes can metabolize EGAEs in the liver, skin and testis [13,[16][17][18]. The hematotoxicity studies of equimolar doses of BE, butoxyacetic aldehyde, and BAA revealed that the effects of all the three chemicals did not differ signifi cantly, which indicates that the interconversion of these chemicals is an effi cient metabolic process in vivo [13].…”
Section: Calculation Of Pka Log P and Log D Valuesmentioning
confidence: 99%
“…EGAEs can produce systemic toxicity, including spermatotoxic, teratogenic, and hematological effects, following oxidation to their corresponding aldehydes and alkoxyacetic acids (AAAs) by alcohol dehydrogenase (ADH) and aldehyde dehydrogenase (ALDH), respectively [13,15]. These enzymes can metabolize EGAEs in the liver, skin and testis [13,[16][17][18]. The hematotoxicity studies of equimolar doses of BE, butoxyacetic aldehyde, and BAA revealed that the effects of all the three chemicals did not differ signifi cantly, which indicates that the interconversion of these chemicals is an effi cient metabolic process in vivo [13].…”
Section: Calculation Of Pka Log P and Log D Valuesmentioning
confidence: 99%
“…The explanation the biological basis of the interactions between ethanol and EGAEs may be related to the metabolism of these compounds. The glycol ethers, especially EE, BE, and 2-phenoxyethanol, are metabolized in vitro by rat hepatic and cutaneous cytosolic preparations in the reaction involving ADH and ALDH in both tissues [35]. Hepatic cytosol metabolizes ethanol in preference to intermediate chainlength EGAEs, whereas the skin cytosol preferentially metabolizes the glycol ethers.…”
Section: Discussionmentioning
confidence: 99%
“…The rates of ADH oxidation by rat liver cytosol were the greatest for ethanol followed by EE and BE. In contrast, the order of metabolism by rat skin cytosolic fraction was changed to BE > EE > ethanol [35]. Although skin contains enzymes that have the capacity to biotransformation EGAEs localized in the basal layer of the epidermis [36], the physicochemical properties of these compounds result in rapid penetration and distinct reduction in dermal metabolism during their percutaneous absorption [37].…”
Section: Discussionmentioning
confidence: 99%
“…40 In addition, it has been shown that the potential for first-pass dermal metabolism during absorption is reduced if the physicochemical properties of the chemical enable rapid penetration. 41 …”
Section: Skin Metabolismmentioning
confidence: 99%